Teacher strategies in utilizing learning media: a descriptive qualitative case study in elementary schools - Sarman Sarman; Nasir Usman; Suparta Rasyid; Muhammad Aulia (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
In the context of Simeulue Regency, Aceh, teachers are required to adapt to these limitations by developing practical strategies for utilizing available learning media. This study aims to explore and analyze teacher strategies in utilizing learning media, focusing on the types of media used, instructional planning, classroom implementation, and perceived effects on student engagement and learning processes. This research employed a descriptive qualitative approach with a case study design conducted in three public elementary schools (SDN 8, SDN 13, and SDN 14 Simeulue). Data were collected through classroom observations, in-depth interviews with nine teachers and three school principals selected purposively, and documentation analysis. The data were analyzed using thematic analysis involving data reduction, categorization, and interpretation to identify recurring patterns of strategy use. The findings indicate that teachers predominantly utilize visual media (pictures and charts), real objects from the surrounding environment, and simple digital media. These strategies are perceived by teachers to enhance student motivation, participation, and conceptual understanding, as reflected in increased classroom interaction, student responsiveness, and attentiveness during learning activities. However, the effectiveness of media utilization is influenced by supporting factors such as teacher creativity and school leadership support, as well as inhibiting factors including limited facilities and teachers’ digital competencies. This study contributes to a contextual understanding of how learning media are strategically utilized in resource-limited elementary schools and highlights that media function as pedagogical supports rather than determinants of measurable academic achievement. The findings suggest that sustainable media utilization requires continuous professional development and institutional support tailored to rural school contexts.